1980
DOI: 10.1099/00222615-13-1-89
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation and Identification of Bacteroides Spp. From the Normal Human Gingival Flora

Abstract: (1972) was followed in all essential aspects; incubation was at 37°C in an atmosphere of H2 90% and COZ 10%. A slope of Simmons citrate medium seeded with Pseudomonas aeruginosa was included in each jar as a control.Specimens. Sterile toothpicks were used to collect samples of subgingival plaque from 20 normal healthy adults. The subjects were medical students aged 19-20 years; none had any gross oral or dental pathology and none was receiving antibiotic therapy.Isolation of Bacteroides. The methods and media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 13 publications
0
19
1
1
Order By: Relevance
“…The common vaginal species were, however, similar to the oral species isolated from subgingival plaque; in a parallel study (Duerden, 1980b) the commonest oral species were B. oralis, B. melainogenicus ss. melaninogenicus and ss.…”
Section: Discussionmentioning
confidence: 99%
“…The common vaginal species were, however, similar to the oral species isolated from subgingival plaque; in a parallel study (Duerden, 1980b) the commonest oral species were B. oralis, B. melainogenicus ss. melaninogenicus and ss.…”
Section: Discussionmentioning
confidence: 99%
“…1) thus revealed no drastic differences in growth dynamics of P. gingivalis, indicating that this bacterium can grow nearly equally under both conditions. This is noteworthy, given that this organism is classified as a strictly anaerobic bacterium and that exclusively anaerobic conditions are recommended to grow the organism (Duerden, 1980;Loesche et al, 1992). Our laboratory and previous studies have demonstrated that P. gingivalis can withstand prolonged exposure to oxygen; thus, clinical samples predicted to contain this bacterium can be stored for a short time in the presence of low concentrations of oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…High levels of toxin lyses cells as the pores formed by the toxin allow cytoplasmic contents to leak out (24). Of interest was the identification of a hypothetical protein belonging to Bacteroides eggerthii, a member of the Bacteroides genus that has been isolated from human feces (3,13). The relevance of identifying this protein from C. ureolyticus was that the bacterium was previously a member of the Bacteroides genus.…”
Section: Effect Of C Ureolyticus Unswcd Infection and Cytokines On Imentioning
confidence: 99%